The new radiation-hard plastic scintillators with diffusion enhancers and 3-hydroxyflavone derivatives - Velmozhnaya, E.S.; Gurkalenko, Yu.A.; Eliseev, D.A.; Zhmurin, P.N.; Lebedev, V.N.; Pereymak, V.N. (Functional Materials, 2016)
New mechanically strong compositions of radiation-hard plastic scintillators with diffusion enhancers and primary dopants with the large Stokes shift are proposed. The new PS has 3 times greater radiation hardness in comparison with the analogues. In order to impart the mechanical strength, the PS are produced on spatially cross-linked polystyrene base.